A brief note on compactness of composition operators on H2. Issue 1 (2nd January 2019) - Akeroyd, John R.; Dutta, Arnab
ABSTRACT: Let be a univalent (analytic) mapping from the unit disk into itself. Under a certain regularity condition on the bundary of, we show that the composition operator is compact on the Hardy space if and only if